CD4 effector T cell expansion to identify objective responses to the CD40 agonist mitazalimab in combination with modified FOLFIRINOX (mFFX) as first-line therapy for metastatic pancreatic ductal adenocarcinoma (mPDAC) in the OPTIMIZE-1 study - Wattenberg, Max Miller; Smith, Karin Enell; de Coaña, Yago Pico; Jimenez, David Gomez; Ambarkhane, Sumeet Vijay; Ellmark, Peter ; 0000-0002-6687-1250; Beatty, Gregory Lawrence (2024)
Background: CD40 agonists have the potential to enhance the efficacy of standard of care chemotherapy and to trigger antitumor immunity. Preclinical models indicate that the success of this approach depends on appropriate sequencing of chemotherapy with a CD40 agonist. Preliminary efficacy results from the OPTIMIZE-1 Phase II study (NCT04888312) combining mitazalimab (anti-CD40) with mFFX chemotherapy in patients with mPDAC have been previously reported. Here, we investigated immunological determinants associated with favorable outcomes with this combination therapy. Methods: Newly diagnosed, chemotherapy-naive patients with mPDAC received mitazalimab (900 mg/kg) on day 1 prior to beginning an every 2-week mFFX regimen on day 8, followed by mitazalimab 48 hours later. Tumor response was determined using RECIST v1.1 criteria. Peripheral blood was analyzed for selected cytokines and chemokines and by flow cytometry to assess changes in leukocyte subsets including B cells, monocytes, T cells, and NK cells. Flow cytometric data from evaluable patients were subjected to unsupervised hierarchical clustering to identify immune subsets. A classifier was generated from an interim dataset (n=21) using a random forest model to predict cell populations and their association with tumor response, which were then applied to the full dataset (n=47). Results: Mitazalimab triggered an expected immune response characterized by transient cytokine (IFNg and MCP-1) release and B cell depletion. Chemotherapy caused a reduction in classical monocytes and proliferating CD4+ T cells. Both mitazalimab and chemotherapy caused a transient reduction in circulating dendritic cells and NK cells. Tumor response was associated with an expansion in the frequency of effector CD4 T cells (p, 0.0001) at day 8 after receiving mitazalimab. In a blinded analysis based on the classifier, CD4 T cell expansion was linked to an early tumor response to treatment (accuracy 70%, sensitivity 68%, specificity 72%). Conclusions: Mitazalimab and mFFX differentially modulate immune responses in patients with mPDAC. Pharmacological analyses identify mitazalimab-induced expansion of CD4 effector T cells one week after first administration as a correlate of treatment outcomes. These data suggest the contribution of mitazalimab to tumor responses, and further substantiate a priming dose of mitazalimab, prior to administering chemotherapy. Research Sponsor: Alligator Bioscience.
Publisher Copyright: © (2024), (Lippincott Williams and Wilkins). All rights reserved.